2020
DOI: 10.3390/app10030744
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Performance of Two Rapid Methods for On-Site Control of Microbial and Biofilm Contamination

Abstract: (1) Background: The validation of hygiene procedures in food industries is paramount to ensure that food contact surfaces are properly decontaminated before production. Rapid, sensitive and reliable tools are needed for routine hygiene validation in order to increase food safety levels. Two novel tools for biofilm detection (TBF 300) and detection of low levels of microbial contamination (FreshCheck) have been assessed. (2) Methods: Biofilms of relevant food pathogens: Listeria monocytogenes and Salmonella spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Biofilm growth was seen not covering the entire 96-well base plate (Fig. 1), similar to a previous study in which the biofilm was observed to coagulate in the center and along the 96-well plate wall 15 . On the other hand, more biofilm was formed and suspend on the media than on stainless steel (Fig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Biofilm growth was seen not covering the entire 96-well base plate (Fig. 1), similar to a previous study in which the biofilm was observed to coagulate in the center and along the 96-well plate wall 15 . On the other hand, more biofilm was formed and suspend on the media than on stainless steel (Fig.…”
supporting
confidence: 89%
“…The stainless surface is hydrophilic and has a negative charge at neutral pH. The surfaces of bacterial cells also have a negative charge, making it difficult for bacteria to colonize these surfaces 15 .…”
mentioning
confidence: 99%
“…Despite its potential for testing antibiotic compounds in a high-throughput method, the use of 96-well microplates leads to the development of biofilms covering a quite small area with no control on the biofilm growing on the walls of the microplate. This makes a direct inspection difficult or impossible [19]. Additionally, some authors pooled together the scraped biofilm contents of three wells to have a single replicate [53].…”
Section: Developing Strongly Attached Biofilmsmentioning
confidence: 99%
“…All methods for growing biofilms have advantages and drawbacks, but the choice of a method also depends on the natural biofilm growth conditions that are mimicked. The existing methods are characterised by different static or hydrodynamic conditions influencing the conditioning, attachment, colonization and detachment of the biofilm [19]. For instance, flow cells can mimic the condition of a piping system, while a tube can be representative of a temporary storage tanks in industries [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation